Pedagogical conditions of future primary school teachers’ culturological training - Вінник, Тетяна Олександрівна (ScienceRise: Pedagogical Education, 2016)
In the article is emphasized the topicality and importance of culturological training of the future teachers of primary school. The author tries to ground pedagogical conditions of this process on the base of results of current studies and analysis of scientific-pedagogical sources. The first condition is a guaranteeing of positive motivation of the future teachers of primary school. It is directed on overcoming of contradictions and negative stereotypes of culturological activity and formation of internal motivation for mastering the culturological knowledge and skills, development of cognitive activity and consciousness of the importance of reflexive position in personal and professional improvement. The second condition is a consciousness, understanding and mastering by the future teachers of the system of knowledge about culturological teaching and skills of its practical use in the context of modern requirements to the professional-pedagogical activity and personal qualities of teacher of the primary classes. The third condition is an involvement of the future teachers in active culturological activity. It is directed on the rational choice and combination of traditional and innovative methods and forms of culturological training of students, stimulation of their activity for mastering the structural components of culturological preparedness